Quasi-one-dimensional carbon-based fractal lattices - Lage, L. L.; Latgé, A. (Frontiers in Carbon, 2023)
Fractal systems are considered now as alternative routes of engineering physical properties in the nanoscale. In particular, stable annular quantum corrals have been proved in distinct synthesis procedures and can provide interesting localized and resonant states. Here we present a theoretical description of effective fractal lattices, mainly composed of annular Koch geometries based on carbon atoms, and also on more complex organic molecules described by triangular Sierpinski geometries. A single band tight-binding approach is considered to derive electronic and transport properties. Fractal molecular linear chain composed of fractal Koch quantum corrals are proposed and the electronic transport are discussed based on the complexity of the neighboring hopping. The spatial charge distributions at different energies highlight the contribution of the composing metallic and carbons atoms in the quantum corral features serving as guide to new functionalization applications based on the symmetry and fractal peculiarities of the proposed nanostructured lattices.